The Analysis of Line Sticker Character “Cony Special Edition” - Gitari Jessica; Elda Franzia (Humaniora, 2017)
The method used for this research was qualitative approach and digital survey to respondents. The purpose was to find out the function of visual in LINE sticker of Cony Special Edition to help the communication between users. The analysis method used was semiotic methods. The result of this analysis is the understanding of LINE sticker of Cony Special Edition usage that managed to represent user’s expression while chatting in their chat room. Top use characters by the user are a character to express the emotion of touch with gratitude, being cornered or alone, mocking, sad and hopeless, and angry until eager to break something. This Cony Special Edition LINE sticker has become one of the objects of communications by its users. It is considered to becoming an attractive communication tool to its user.